The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3354/meps09265
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive consequences of environment-driven variation in Adélie penguin breeding phenology

Abstract: Adélie penguins Pygoscelis adeliae exhibit phenological variability across their geographic range due to fixed and variable forcing factors acting differentially on populations. Shifts in breeding phenology can be indicative of environmental change when cues for breeding initiation are tightly linked with environmental conditions. Adélie penguins on opposite sides of Antarctica display contrasting trends in clutch initiation dates, with different explanations of underlying causes. To make comparisons possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…This interaction relationship points to the importance of local wind speed on either food resources or nest site conditions. A previous study of Adélie penguins in East Antarctica also linked interannual variation in breeding phenology to the AAO, air temperature, wind speed and direction (Emmerson et al 2011). This suggests our predictor variables are not unique to Adélie chicks at Humble Island and can impact many parts of the Adélie life cycle.…”
Section: Climate and Weather Interaction Predictor Variables Of Cfmmentioning
confidence: 90%
See 1 more Smart Citation
“…This interaction relationship points to the importance of local wind speed on either food resources or nest site conditions. A previous study of Adélie penguins in East Antarctica also linked interannual variation in breeding phenology to the AAO, air temperature, wind speed and direction (Emmerson et al 2011). This suggests our predictor variables are not unique to Adélie chicks at Humble Island and can impact many parts of the Adélie life cycle.…”
Section: Climate and Weather Interaction Predictor Variables Of Cfmmentioning
confidence: 90%
“…For example, Adélie penguins Pygoscelis adeliae are a circum-Antarctic, sea-ice-dependent species whose populations have declined precipitously throughout the northern WAP (Ainley 2002). The hypothesized main drivers of the trends in Adélie penguin populations and demographics include large-scale climate shifts, local weather, and food availability (Patterson et al 2003, Forcada & Trathan 2009, Emmerson et al 2011, Trivelpiece et al 2011. To gain insight into Antarctic ecosystem function in a region of rapid change, the long-term trend, and also the drivers of interannual ecosystem variability must be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Penguins Pygoscelis adeliae arrive later at their breeding colonies on Béchervaise Island, East Antarctica (Emmerson et al 2011). Although later arrival did not appear to influence breeding success, it did lead to reduced courtship and egg-laying, later clutch initiation, later parent departure for foraging trips and later chick-hatching.…”
Section: Seabird Migration Phenologymentioning
confidence: 96%
“…Similarly, migration timing in the penguins located in the Antarctic and subantarctic has not changed significantly over time (Barbraud and Weimerskirch 2006;Crawford et al 2006;Emmerson et al 2011;Saraux et al 2011) though breeding and migration timing are known to vary by latitude (Ainley 2002;Emmerson et al 2011).…”
Section: Seabird Migration Phenologymentioning
confidence: 99%
“…How can these behavioral changes be explained? Several studies on seabirds have shown that mass gain at sea is positively related to foraging trip duration (e.g., Weimerskirch 1995; Barlow and Croxall 2002;Emmerson et al 2011), because foraging trip lengths may vary depending on food availability and foraging success (e.g. , Cairns 1987;Williams 1995).…”
Section: Foraging Trip Durationmentioning
confidence: 99%